(untitled) (Medico Legal Update, 2021)
Background: Galium aparine has a long history of use as an alternative medicine and is still used widely by modern herbalists. It is a fabulous diuretic that is often taken to treat skin problems. It treats many problems such as seborrhoea, eczema, psoriasis. It also acts as a great detoxifying agent in life-threatening ailments like cancer. Skin cancer is the most common type of cancer in light skinned populations around the world. Aim: The aim of the study was to evaluate the anticancer efficacy of greensynthesised silver nanoparticles (AgNPs) of Gallium aparine extract. Method: The green part of the plant G.aparne extracted with ethanol 70%, then divided into four fractions to prepare stable AgNPs . Results: Several tests were performed to examine the extracts and AgNPs, including SEM,FTIR and UVVS. Scanning electron microscope(SEM)micrographs showed that the diameters range of AgNPs formed were from 35-110 nm.Fourier transform infrared (FTIR) shows that there were two functional groups, the aromatic (C=C) and hydroxyl (– OH), groups may be involve in the fabrication of AgNPs. UV-VS shows that there were a peaks at 298,448, 534, 606, 648, for nanoscale petroleum ether extract. These peaks may beindicate the synthesis of AgNPs. Different concentrations (6.225 - 400 µg/ml), of petroleum ether extract and its green AgNPswere tested as anti-skin cancer, the nanoparticles had appositive effect against cancer, the IC50 for the petroleum ether extract was 730.2 and 116.5 of normal cell line (WRL 68) and cancer cell line (A375), respectively,while the IC50 for the AgNPs of Gallium aparine extract was 294.4 and 77.03of normal cell line (WRL 68) and cancer cell line (A375)respectively. Discussion: This indicates that the G. aparine extract is a good biological carrier for synthesizing silver nanoparticles which has potential for various biomedical and pharmaceutical applications. Conclusion: AgNPs have been successfully synthesized using G . aparian extract, The nanoparticles have shown good anticancer activity towards human skin cancer cells.